KECERDASAN EMOSIONAL SISWA TERHADAP PRESTASI BELAJAR MATEMATIKA DI MASA PANDEMI - Iqbal, Muh; Hamid, Hariaty; Susanti, Dwi (Mathematics Education And Application Journal (META), 2022)
The percentage of emotional intelligence that affects the mathematics learning achievement of class XI-MIA students of SMA Muhammadiyah Tarakan during the Covid-19 pandemic (Corona Virus Desaster-19) was the purpose of this study. A quantitative approach with a survey method had chosen as the research method to answer the problem formulation. Questionnaires and documentation had chosen as data collection techniques. Proportionate random sampling had used to select the research sample from the class XI-MIA population of SMA Muhammadiyah Tarakan had four classes consisting of 127 students. The research sample obtained was 96 students. Descriptive and inferential statistical analysis had chosen as the data analysis technique. Descriptive analysis was used to describe the research data obtained, while inferential statistical analysis was used to answer the problem formulation using hypothesis testing. Before carrying out the hypothesis test, the prerequisite assumptions were tested, showing that the data were normally distributed and had a linear pattern. Furthermore, the hypothesis test was obtained that ð‘¡ð‘–ð‘¡ð‘¢ð‘›ð‘” ð‘¡ð‘¡ð‘Žð‘ð‘’ð‘™ , which is 2.666 1.98525, means that emotional intelligence has a significant effect on learning achievement in mathematics. 0.07 is the value of the coefficient of determination which means that students' mathematics learning achievement during the pandemic is influenced by 7% by emotional intelligence.Keywords: Emotional Intelligence, Mathematics Learning Achievement, during the pandemic.AbstrakBesarnya presentase kecerdasan emosional yang mempengaruhi prestasi belajar matematika siswa kelas XI-MIA SMA Muhammadiyah Tarakan pada masa pandemi Covid-19 (Corona Virus Desaster-19) merupakan tujuan dari penelitian ini. Pendekatan kuantitatif dengan metode survei dipilih sebagai metode penelitian untuk menjawab rumusan masalah. Angket dan dokumentasi dipilih menjadi teknik pengumpul data. Proportionate random sampling digunakan untuk memilih sampel penelitian dari populasi kelas XI-MIA SMA Muhammadiyah Tarakan sebanyak 4 kelas yang terdiri dari 127 siswa. Perolehan sampel penelitian sebanyak 96 siswa. Analisis statistik deskriptif dan inferensial dipilih sebagai teknik analisis data. Analisis deskriptif digunakan untuk mendeskripsikan data penelitian yang diperoleh, sedangkan analisis statistik inferensial digunakan untuk menjawab rumusan masalah dengan menggunakan uji hipotesis. Sebelum melaksanakan uji hipotesis dilakukan uji asumsi prasyarat, yang menunjukkan bahwa data telah berdistribusi normal dan berpola linier. Selanjutnya uji hipotesis diperoleh bahwa ð‘¡ð‘–ð‘¡ð‘¢ð‘›ð‘” ð‘¡ð‘¡ð‘Žð‘ð‘’ð‘™, yaitu 2,666 1,98525, yang artinya kecerdasan emosional berpengaruh secara signifikan terhadap prestasi belajar matematika. 0,07 merupakan nilai dari koefisien determinasi yang berarti prestasi belajar matematika siswa pada masa pandemi dipengaruhi sebesar 7% oleh kecerdasan emosional.Kata kunci: Kecerdasan Emosional, Prestasi belajar matematika, Masa pandemi